Platitudes and opacity: Explaining philosophical uncertainty - Eriksson John; Francén Ragnar (Belgrade Philosophical Annual)
In The Moral Problem, Smith defended an analysis of moral judgments based on a number of platitudes about morality. The platitudes are supposed to constitute conceptual constraints which an analysis of moral terms must capture "on pain of not being an analysis of moral terms at all". This paper discusses this philosophical methodology in light of the fact that the propositions identified as platitudes are not obvious truths-they are propositions we can be uncertain about. This, we argue, is a kind of fundamental philosophical uncertainty, and we develop an account of fundamental uncertainty (for both philosophical and other issues). The key to understand such uncertainty, on our view, is conceptual opacity-i.e., that the content and reference of concepts is not necessarily transparent to competent concept users. We argue that Smith's own view of conceptual analysis in TMP provides one plausible explanation of fundamental uncertainty. However, we also argue that another potential explanation is conceptual indeterminacy. If some fundamental philosophical uncertainties are best explained in this way, the implication is that there is no determinately correct analysis of the target terms and concepts.